To expand the expression \((-4x-3)(3x^2-x-1)\), we will distribute each term in the first polynomial to each term in the second polynomial.
-
Distributing \(-4x\):
- \(-4x \cdot 3x^2 = -12x^3\)
- \(-4x \cdot (-x) = 4x^2\)
- \(-4x \cdot (-1) = 4x\)
-
Distributing \(-3\):
- \(-3 \cdot 3x^2 = -9x^2\)
- \(-3 \cdot (-x) = 3x\)
- \(-3 \cdot (-1) = 3\)
Now, we will combine these results:
\[ -12x^3 + (4x^2 - 9x^2) + (4x + 3x) + 3 \]
This simplifies to:
\[ -12x^3 - 5x^2 + 7x + 3 \]
Thus, the polynomial in standard form is:
\(-12x^3 - 5x^2 + 7x + 3\)